Synthesis and Evaluation of 18F-INER-1577-3 as a Central Nervous System (CNS) Histone Deacetylase Imaging Agent - Li, Ming-Hsin; Chang, Han-Chih; Feng, Chun-Fang; Yu, Hung-Wen; Shiue, Chyng-Yann (Current Medical Imaging, 2020)
Background: Epigenetic dysfunction is implicated in many neurologic, psychiatric and oncologic diseases. Consequently, histone deacetylases (HDACs) inhibitors have been developed as therapeutic and imaging agents for these diseases. However, only a few radiotracers have been developed as HDACs imaging agents for the central nervous system (CNS). We report herein the synthesis and evaluation of [18F]INER-1577-3 ([18F]5) as an HDACs imaging agent for CNS. Methods: [18F]INER-1577-3 ([18F]5) was synthesized by two methods: one-step (A) and two-step (B) methods. Briefly, radiofluorination of the corresponding precursors (11, 12) with K[18F]/K2.2.2 followed by purifications with HPLC gave ([18F]5). The quality of [18F]INER- 1577-3 synthesized by these methods was verified by HPLC and TLC as compared to an authentic sample. The inhibitions of [18F]INER-1577-3 and related HDACs inhibitors on tumor cells growth were carried out with breast cancer cell line 4T1 and MCF-7. The whole-body and brain uptake of [18F]INER-1577-3 in rats and AD mice were determined using a micro-PET scanner and the data was analyzed using PMOD. Results: The radiochemical yield of [18F]INER-1577-3 synthesized by these two methods was 1.4 % (Method A) and 8.8% (Method B) (EOB), respectively. The synthesis time was 115 min and 100 min, respectively, from EOB. The inhibition studies showed that INER-1577-3 has a significant inhibitory effect in HDAC6 and HDAC8 but not HDAC2. PET studies in rats and AD mice showed a maximum at about 15 min postinjection for the whole brain of a rat (0.47 ± 0.03 %ID/g), SAMP8 mice (5.63 ± 1.09 %ID/g) and SAMR1 mice (7.23 ± 1.21 %ID/g). Conclusion: This study showed that INER-1577-3 can inhibit tumor cell growth and is one of a few HDACs inhibitors that can penetrate the blood-brain barrier (BBB) and monitor HDAC activities in AD mice. Thus, [18F]INER-1577-3 may be a potent HDACs imaging agent, especially for CNS.
Keywords: Epigenetic modifications